THE EFFECT OF MUNG BEAN SPROUT EXTRACT AS A NATURAL PLANT GROWTH REGULATOR ON THE GROWTH OF SUGARCANE BUDCHIP (Saccharum officinarum L.) SEEDLINGS - Sepdian Luri Asmono; Nur uhammad Haqiqi; Abdurrahman Salim (Universitas Wahid Hasyim, 2023)
This study aims to determine the effect of several concentrations of mung bean sprouts or bean sprouts extract on the growth of sugarcane bud chip seedlings, as well as to determine the most optimal concentration in stimulating the growth of sugarcane seedlings. Mung bean sprouts are known to contain the endogenous hormone auxin which can stimulate plant growth. This research was conducted using a non-factorial randomized block design. There are 5 concentration levels of bean sprout extract, including T0 (control), T1 (20%), T2 (40%), T3 (60%), T4 (80%). Parameters observed include the number of tillers, stem height, number of leaves, leaf length and root length. The results showed that bean sprout extract significantly affected the growth of seedlings from all parameters. The concentration of 20% bean sprout extract is the optimal concentration because it produces the highest number of tillers with an average of 8.80 tillers, the highest stem with an average of 18.00 cm, the largest stem diameter is 0.91 cm, the highest number of leaves is 8, 20 strands, the longest leaf is 73.3 cm, and the longest root is an average of 26.3 cm.